Polarisation Independent Split Ring Frequency Selective Surface - Cahill, Robert; Zabri@Suhaimi, Siti Normi; Schuchinsky, Alexander G. (The Institution of Engineering and Technology, 2013)
A frequency selective surface (FSS) is described which exhibits coincident spectral responses for TE and TM polarisation when the FSS operates at 45° incidence. The structure consists of two closely spaced arrays of ring elements with the conductor split at one or two locations to provide independent control of the resonances for the vertical and horizontal field directions. The FSS is designed to diplex two channels separated by an edge of a band ratio of 1.7:1 and yield a common - 10 dB reflection bandwidth of 10.2%. Measured and numerical results are shown to be in good agreement over the frequency range 9-12 GHz.